Temporal Summation Predicts De Novo Contralateral Pain After Cordotomy in Patients With Refractory Cancer Pain. Issue 1 (January 2022) - Treister, Roi; Honigman, Liat; Berger, Assaf; Cohen, Ben; Asaad, Israa; Kuperman, Pora; Tellem, Rotem; Hochberg, Uri; Strauss, Ido
Abstract : BACKGROUND: Percutaneous cervical cordotomy (PCC), which selectively interrupts ascending nociceptive pathways in the spinal cord, can mitigate severe refractory cancer pain. It has an impressive success rate, with most patients emerging pain-free. Aside from the usual complications of neurosurgical procedures, the risks of PCC include development of contralateral pain, which is less understood. OBJECTIVE: To evaluate whether sensory and pain sensitivity, as measured by quantitative sensory testing (QST), are associated with PCC clinical outcomes. METHODS: Fourteen palliative care cancer patients with severe chronic refractory pain limited mainly to one side of the body underwent comprehensive quantitative sensory testing assessment pre-PPC and post-PCC. They were also queried about maximal pain during the 24 h precordotomy (0-10 numerical pain scale). RESULTS: All 14 patients reported reduced pain postcordotomy, with 7 reporting complete resolution. Four patients reported de novo contralateral pain. Reduced sensitivity in sensory and pain thresholds to heat and mechanical stimuli was recorded on the operated side ( P = .028). Sensitivity to mechanical pressure increased on the unaffected side ( P = .023), whereas other sensory thresholds were unchanged. The presurgical temporal summation values predicted postoperative contralateral pain ( r = 0.582, P = .037). CONCLUSION: The development of contralateral pain in patients postcordotomy for cancer pain might be due to central sensitization. Temporal summation could serve as a potential screening tool to identify those who are most likely at risk to develop contralateral pain. Analysis of PCC affords a unique opportunity to investigate how a specific lesion to the nociceptive system affects pain processes.